Genome typing, histopathology, and evolution of BPV30, a novel Xipapillomavirus type isolated from Bovine papilloma in Costa Rica. (April 2022) - Alfaro-Mora, Ramses; Zobba, Rosanna; Antuofermo, Elisabetta; Burrai, Giovanni Pietro; Solinas, Roberto; Dolz, Gaby; Pittau, Marco; Alberti, Alberto
Abstract: Xipapillomavirus includes a group of viruses almost exclusively reported in both beef cattle and dairy breeding, in which they induce papillomatosis and occasionally malignant tumors. Bovine papillomaviruses (BPVs) infection impacts greatly on animal productions, and this is amplified by their cosmopolitan distribution. Cutaneous proliferative lesions in bovines can relate to leather depreciation and impaired milk production by giving rise to obstruction of the teat and hygiene limitations, often leading to hemorrhagic mastitis. This study reports the identification of a novel Xipapillomavirus type associated with udder papilloma in a Jersey cow in Costa Rica. Viral genome was fully sequenced and molecularly characterized. Histopathology and viral phylogeny and evolution are also presented and discussed by comparison with already described BPVs. Based on results, a novel Xipapillomavirus type, namely BPV30, is proposed. BPV30 is a typical Xipapillomavirus 2 most similar to BPV12, from which it separated roughly 18 million years ago. The absence of E6 and the presence of E10 in BPV30 confirm an E6 loss occurring along the clade leading to BPV12. The identification of this novel BPV is fundamental to the development of specific prophylactic tools, which represent the most effective weapon to fight viral circulation, to prevent infections, and eventually controlling associated proliferative lesions. Highlights: A novel Xipapillomavirus (BPV30) was identified associated to cutaneous udder papilloma in cattle. BPV30 genome has been fully sequenced and characterized and its evolutionary history fully reconstructed. BPV30 evolution confirm the loss of E6 along the clade leading to BPV12. This study is fundamental to development of tools to control bovine papillomatosis.